2012
DOI: 10.1590/s1678-77572012000400011
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of endodontic sealers of different bases

Abstract: ObjectiveTo assess the setting time (ST), flow (FL), radiopacity (RD), solubility (SB) and dimensional change following setting (DC) of different sealers (AH Plus®, Polifil, Apexit Plus®, Sealapex®, Endométhasone® and Endofill® according to American National Standards Institute/American Dental Association (ANSI/ADA) Specification 57. Material and methodsFive samples of each material were used for each test. For ST, cast rings were filled with sealers and tested with a Gilmore needle. For FL, the sealer was pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
0
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 27 publications
10
51
0
15
Order By: Relevance
“…Acording to ISO 6876 [11] , working time should be less than 30 min and setting time from 30 min to 72 h. In the present study, all groups presented setting time in accordance with ISO requirements, but higher working time than the standard. The values of the present study were similar to Apexit Plus [4] . ISO 6876 [11] requires that a sealer should not shrink more than 1% nor swell more than 0.1%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Acording to ISO 6876 [11] , working time should be less than 30 min and setting time from 30 min to 72 h. In the present study, all groups presented setting time in accordance with ISO requirements, but higher working time than the standard. The values of the present study were similar to Apexit Plus [4] . ISO 6876 [11] requires that a sealer should not shrink more than 1% nor swell more than 0.1%.…”
Section: Discussionsupporting
confidence: 86%
“…The most frequently used endodontic sealers are resin-based sealers, zinc oxide-eugenol sealers, calcium hydroxide-containing sealers, glass ionomerbased sealers, and mineral trioxide aggregate (MTA)-based sealers [2] . These materials present in their compositions filler particles that provide better mechanical properties, rheological adjustment, and radiopacity [1,[3][4][5][6] . Bismuth compounds are often used in root canal sealers to provide radiopacity [7,8] and have been used in Grossman's sealer [9] .…”
Section: Introductionmentioning
confidence: 99%
“…28 Previous reports on physicochemical properties highlighted that the presence of epoxy resin is responsible for increasing sealer viscosity. 21,26 In this study, we also observed a lower volume of sealer using the active lateral condensation technique than that using the passive lateral condensation technique, regardless of the sealer used, probably because of the use of finger spreaders in the active lateral condensation technique to create space for inserting a higher number of gutta-percha cones into the root canal, 13,34 thereby decreasing the volume of gaps that occur because of sealer dissolution and the lack of filling root canal irregularities. 22,35 Although a spreader cannot reach the apical 1 mm, it exerts a force that results in changes in the apical 1 mm.…”
mentioning
confidence: 58%
“…This result could be ascribed to the fact that these sealers have a higher flow rate than the other sealers studied. 24,25,26 . The flowability of the sealers is an important property that can determine the extent of filling of anatomical irregularities and spaces between the main cone and accessory cones to improve the effectiveness of root canal fillings.…”
Section: 10mentioning
confidence: 99%
“…Marin-Bauza et al. [14] tested the setting time, f low, radiopacity, solubility, and dimensional alteration of si x endodontic sealers (AH Plus, Polifil, Apexit Plus, Sealapex, Endomethasone, and Endofill). AH Plus sealer showed characteristics within the guidelines established by ANSI/ADA.…”
Section: Solubilitymentioning
confidence: 99%